Relationship between hand hygiene behavior and Staphylococcus aureus colonization on cell phones of nurses in the intensive care unit - Meri Afridayani; Yohana Ika Prastiwi; Khudazi Aulawi; Ibrahim Rahmat; Hera Nirwati; Haryani Haryani (Belitung Nursing Journal, 2021)
Background: Healthcare-Associated Infections (HAIs) are infections that often occur in hospitals with Staphylococcus aureus as the primary cause. Staphylococcus aureus is usually found on nurses' hands and easily transferred by contact. Cell phones can be a convenient medium for transmitting bacteria. Accordingly, hand washing is one of the effective ways to prevent the transmission of Staphylococcus aureus. Objective: This study aimed to determine the relationship between hand hygiene behavior and the colonization of Staphylococcus aureus on cell phones of nurses in the intensive care unit of the academic hospital. Methods: This was an observational study with a cross-sectional design conducted from December 2019 to January 2020. The observations of hand hygiene behaviors were performed on 37 nurses selected using total sampling. Colonization of bacteria on each nurses' cell phone was calculated by swabbing the cell phones' surface. Colony counting was done using the total plate count method. Spearman Rank test and Mann Whitney test were used for data analysis. Results: The nurses' hand hygiene behavior was 46.06%. Staphylococcus aureus colonization was found on 18.2% of the nurses' cell phones. However, there was no significant relationship between the nurses' hand hygiene behavior and the colonization of Staphylococcus aureus on their cell phones. Conclusion: The hand hygiene behavior of nurses was still low, and there was evidence of Staphylococcus aureus colonization on their cell phones. As there was no relationship between the nurses' hand hygiene behavior with the colonization of Staphylococcus aureus on the cell phones, further research is needed to determine if there is an increase or decrease in colonization before and after regular observations.